Perancangan Antarmuka Pengguna Sepatubersih.com berbasis Perangkat Bergerak menggunakan Metode Goal-Directed Design (GDD) - Agung Adhi Nugroho; Hanifah Muslimah Az-Zahra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Sepatu Bersih is a service provider that focuses on shoe washing and treatment has a website platform at www.sepatubersih.com which help their customer check the status of service provided about their shoe's treatment order. The platform itself currently considered less effective and it's hoped that the presence of other platform such as mobile apps can help with the shortcomings that existed in the previous platform. Goal-Directed Design (GDD) it's a method that can provide a solution for this case. In making the application, its necessary to research the users and stakeholder, especially the user interface before the application is made so that later the right application is in accordance within the goals or desires of Sepatu Bersih. Goal-Directed Design has 6 stages in its application, the first one is research to get input from users and stakeholders in the form of problems and expectations. The second one is modeling which provides personas and an overview of user and stakeholders, requirements is the third stage that will describe the needs of users. The fourth stage is a making framework that will provide a blueprint of the interface according to input from both users and stakeholders to be designed. The fifth stage is refinement which will enable to produce a high-fidelity prototype that will be tested and analyzed and later at the last stage which is support. The final evaluation here uses System Usability Scale (SUS) Questionnaire. After the design is done developed using Goal-Directed Design method. The final average value of the System Usability Scale is that the average value of the SUS score is 74, with an Acceptability value above 73 and also gets a Grade Scale in category C category, Adjective Rating is in the Good category.